Penentuan Kulitas Batubara Berdasarkan Nilai Kalor Menggunakan Metode Kalorimetri Isoperibol - denanda, denanda (Jurnal Teknologi dan Inovasi Industri (JTII), 2025)
Coal is an energy source used in various industrial sectors such as Steam Power Plants (PLTU) and Cement Production. Determination of gross calorific value in coal was carried out using a Parr 6200 Calorimeter. This study aims to determine the quality of coal based on gross calorific value using the isoperibol calorimetry method. The results showed that the samples analyzed were included in medium and high quality with Sub-Bituminous A and Sub-Bituminous B coal types with gross calorific values ​​of 5860 cal/g; 5939 cal/; 5765 g/cal; 6002 cal/g; 5990 cal/g; 5723 g/cal; 5864 cal/g; 6219 cal/g; 6054 cal/g; 5986 cal/g.